2016
DOI: 10.7759/cureus.906
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Connective Tissue Disorder Complicated by Polymyositis, Sjogren’s Syndrome, Pleural Effusion and Pericarditis

Abstract: We report a case of a 24-year-old female with a history of asthma and gastroesophageal reflux disease (GERD). She presented to the emergency room with severe chest pain, chest tightness, and shortness of breath following an upper respiratory tract infection. The patient reported that she had a cough and runny nose one week prior to this presentation, followed by a sudden sharp pain in the center of the chest 8/10 in intensity on the visual analog scale and pleuritic in nature, which aggravated by deep breathin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The first diagnosis in 10% had a full blown picture of MCTD (SLE, SS, DM), is similar to a study in Minnesota, USA which reported that the annual incidence of MCTD was 1.9 per 100,000 population. 20 Our study showed that 40% evolved from SLE, 26.7% evolved from RA, 6.7% from SS, and 3.3% evolved from PM to MCTD, similar to a study in Pakistan which found that, over the disease course of 6 years, 10% of patients evolved into SLE. Also this is comparable to the Minnesota study, in which evolution from other connective tissue diseases occurred at 8.5% and 6.3% for SLE and SS, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The first diagnosis in 10% had a full blown picture of MCTD (SLE, SS, DM), is similar to a study in Minnesota, USA which reported that the annual incidence of MCTD was 1.9 per 100,000 population. 20 Our study showed that 40% evolved from SLE, 26.7% evolved from RA, 6.7% from SS, and 3.3% evolved from PM to MCTD, similar to a study in Pakistan which found that, over the disease course of 6 years, 10% of patients evolved into SLE. Also this is comparable to the Minnesota study, in which evolution from other connective tissue diseases occurred at 8.5% and 6.3% for SLE and SS, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…78,113,114 As effusions tend to be small in MCTD, they do not require symptomatic drainage and can resolve with the treatment of underlying disease. 115 MCTD patients are treated with medications controlling specific symptoms, i.e., nonsteroidal anti-inflammatory drugs and antimalarials for arthralgias and myalgias, calcium channel blockers for Raynaud's phenomenon. Short courses of corticosteroids are commonly used and pleural disease is particularly responsive to this treatment.…”
Section: Fluid Characteristics and Clinical Coursementioning
confidence: 99%